Redefining the Contemporary University: Expanding Models, Diverse Campuses, and Evolving Missions - Tas, Murat (Advances in Social Sciences Research Journal, 2025)
The modern university is no longer a fixed, location-based establishment. Rather, it serves increasingly diverse student groups through a wide range of modalities, including online, hybrid, private, public, and for-profit. This conceptual article explores how the structure, governance, and mission of higher education have changed as a result of changes in technology, legislation, and demographics. It emphasizes how data-driven strategies and evaluation frameworks direct institutional evolution by drawing on literature about student participation, accreditation requirements, institutional diversity, online learning, and micro-credentials. The end effect is a more adaptable, inclusive, and results-driven environment that is ready to address the demands of students in the twenty-first century, including the opportunities and difficulties brought on by the COVID-19 epidemic.